TO FORMULATE AND STUDY THE RELEASE KINETICS OF RIVAROXABAN TABLETS USING CO-PROCESSED EXCIPIENTS - KOLWALKAR S; KENY S; SAWAIKAR L; JADHAV A (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The current study aimed at designing, developing, and characterizing orodispersible tablets of Rivaroxaban for treating the blood clots, minimizing the chances of stroke and systemic embolism. Methods: The tablets were prepared by the direct compression method using co-processed excipients (Prosolv® Oro dispersible tablets [ODT] G2, Ludiflash®, Pearlitol). A co-processed excipient is a particle engineering technique where multiple excipients merge at a sub-particle level with the objective to attain functionality improvement as well as masking of the undesirable properties. Results: Various parameters such as thickness, weight variation, hardness, friability, dispersion time, wetting time, disintegration time, content uniformity, and in vitro drug release were evaluated. Fourier-transform infrared spectroscopy analysis revealed no drug-excipient interactions. The presence of sharp peaks in the X-ray diffraction patterns of Rivaroxaban confirms its crystalline nature. Differential Scanning Calorimetry Thermogram of the physical mixture corresponds to the melting point of Rivaroxaban and β-cyclodextrin, suggesting no physical and chemical interaction between the active and the complexing agent. Among all the formulations, FM2 showed the most promising results in terms of disintegration time of 72 Seconds and in vitro drug release of 97 Percent (%) within 20 minutes. Conclusion: The study concludes that the orodispersible tablets of Rivaroxaban complexed with β-cyclodextrin can potentially enhance drug bioavailability and achieve rapid drug intervention.